Fibroblast-directed PET imaging reveals a case of retroperitoneal fibrosis after immunotherapy for metastatic urothelial cancer of the upper tract - L. Gallardo Zamora; F.C. von Rundstedt; C. Wach; W.P. Fendler; I. Maric; K. Herrmann; J.T. Siveke; P.F.-Y. Cheung; V. Grünwald (Urology Case Reports, 2025)
Urothelial carcinomas of the upper urinary tract (UTUC) are relatively rare and challenging to treat. We present a case report of a 55-year-old male patient with high-grade renal UTUC who received adjuvant pembrolizumab immunotherapy. The patient developed retroperitoneal fibrosis as an immune-related adverse event (irAE) following treatment.To better understand the extent of fibrosis, we utilized 68Ga FAPI-46 PET/CT imaging, a radioligand that binds to fibroblast activation protein alpha expressed on activated fibroblasts. The imaging pattern correlated with histopathological findings of fibrotic tissue.This case highlights the limited experience with rare irAEs due to checkpoint inhibitors, such as retroperitoneal fibrosis.